2021
DOI: 10.1038/s41467-021-21614-5
|View full text |Cite
|
Sign up to set email alerts
|

Cells recognize osmotic stress through liquid–liquid phase separation lubricated with poly(ADP-ribose)

Abstract: Cells are under threat of osmotic perturbation; cell volume maintenance is critical in cerebral edema, inflammation and aging, in which prominent changes in intracellular or extracellular osmolality emerge. After osmotic stress-enforced cell swelling or shrinkage, the cells regulate intracellular osmolality to recover their volume. However, the mechanisms recognizing osmotic stress remain obscured. We previously clarified that apoptosis signal-regulating kinase 3 (ASK3) bidirectionally responds to osmotic stre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 73 publications
3
58
0
Order By: Relevance
“…As was the case for BAG2 condensates (Fig. 3b ), previous studies have shown that phase separation in some proteins depends upon a coiled-coil domain as observed for ASK3 under hyperosmotic stress 47 or ORF1 RNA chaperone 48 . Interestingly, the BAG2 phosphorylation site at the first amino acid of the coiled-coil domain, modulates BAG2 phase separation (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…As was the case for BAG2 condensates (Fig. 3b ), previous studies have shown that phase separation in some proteins depends upon a coiled-coil domain as observed for ASK3 under hyperosmotic stress 47 or ORF1 RNA chaperone 48 . Interestingly, the BAG2 phosphorylation site at the first amino acid of the coiled-coil domain, modulates BAG2 phase separation (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…ASK3 bidirectionally responds to changes in osmolality, being phosphorylated and therefore activated under hypoosmotic conditions and in turn dephosphorylated and inactivated under hyperosmotic conditions, consequently regulating cell volume recovery. During hyperosmosis, liquid phase separation of ASK3 is necessary for its inactivation and PAR has been shown to maintain liquidity of those condensates, therefore presenting a supporting factor in osmotic stress regulation ( 140 ). For more detailed information on the involvement of PAR in biomolecular condensate formation, we would like to refer to a recent review article by Leung ( 100 ).…”
Section: Consequences Of Par Heterogeneity: Why Structure and Chain Length Mattermentioning
confidence: 99%
“…Several groups have shown that PAR, a nucleic acid-mimicking biopolymer, can stimulate liquid demixing of IDPs or proteins with low-complexity regions in vitro or in vivo. For instance, a recent publication on apoptosis signal-regulating kinase 3 (ASK3) indicated that PAR could keep ASK3 condensates in the liquid phase and enable cells to sense osmotic stress (Watanabe et al, 2021). LLPS of SG components including fused in sarcoma (FUS), TDP-43, and hnRNP A1 are also regulated by PAR (Altmeyer et al, 2015;Patel et al, 2015;Kam et al, 2018;McGurk et al, 2018a;Duan et al, 2019;Singatulina et al, 2019).…”
Section: Poly(adp-ribose) Affects Protein Phase Separation Behavior Of Sg Componentsmentioning
confidence: 99%